Analgesic effects of high-frequency and low-frequency TENS currents in patients with distal neuropathy - Natalia Kulikova; Al-Zamil Mustafa Khalilovich; Tatiana Konchugova; Andrey Rachin; Tinatin Chkheidze; Detelina Kulchitskaya; Fesyun Anatoliy; Natalia P. Sanina; Elena Ivanova (PAGEPress Publications, 2022)
Currently, diabetes mellitus (DM) is relevant problem, both for its prevalence and complications, including distal polyneuropathy (DPNP). At the same time, discussions continue on analgesic efficacy of transcutaneous electrical nerve stimulation (TENS) in DPNP. Aim of this study was to conduct a multi-faceted assessment of pain syndrome in these patients before and after TENS, taking into account levels of polyneuropathy, its severity and age of patients. The study was conducted in accordance with the research of the Federal State Budgetary Institution of the National Medical Research Center for Rehabilitation and Balneology of the Ministry of Health of the Russian Federation (CTR No. 121040100062-3) and with the permission of the Local Ethics Committee (IRB No. 2 dated 14.01.2021). The study included 75 patients with DM type II with DPNP, which are distributed into 3 groups of 25 people: Group 1a, patients received high-frequency TENS (HF); Group Ib, patients received low-frequency TENS (LF); as control, Group C received a standard method of pharmacological therapy without physiotherapy. Intensity of DPNP was evaluated before and after the course of treatment using a visual analog scale (VAS), the McGill Pain Questionnaire (MPQ), and a graphical linear analysis of pain on the neuropathic pain diagnostic questionnaire 4 (DN4) scale. TENS provides an analgesic effect that may exceed pharmacotherapy in terms of efficacy and safety. There was a 65.9% reduction in neuropathic pain according to VAS after a course of application, with the effects remaining up to 34% during the 6-month follow-up. HF TENS provided a higher significant analgesic effects than LF TENS, as it ensures the reduction of pain syndrome according to VAS by 25.8% (p <0.01), and total estimated characteristics - 35.5% (p <0.01), and touch - in at 58.1% (p = 0.001) and according to the scales of the MPQ (S) and DN4 - by 21% (p = 0.007). The observed differences in analgesic effects between HF TENS and LF TENS are based on analyses of pain in the immediate and long-term follow-up periods of type II DM patients with DPNP. These results, based on summation of the estimated parameters of the international pain scales support expectation of an expansion of the the use of analgesic TENS in aging patients suffering with DM of varying severity and extent of DPNP damage, a goal of great scientific and practical importance.